Specifični simulator JEK - orodje za učinkovito usposabljanje operaterjev - Pribožič, Franc (Strojniški vestnik, 2000)
The acquisition of a full-scope simulator represents a very important achievement the Krško nuclear power plant (NPP). The aim of this paper is to present the use of simulators in the training process and to give some basic information about our plant-specific simulator. Some basic information is provided about the training process for licensed personel and the role of the simulator in the future training activities at Krško NPP.
Keywords: simulatorji; analize; modeliranje; usposabljanje; Nuklearna elektrarna Krško